2013 International Conference on Cyberworlds 2013
DOI: 10.1109/cw.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Virtual Environment for Rugby Skills Training

Abstract: Peer reviewe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Typical examples exist in rugby Brault et al 2010;Miles et al 2013], handball [Vignais et al 2009;Vignais et al 2010], baseball [Fink et al 2009] or tennis [Xu et al 2009]. Most of these studies aimed at analysing the perception-action coupling without considering the accuracy with which the tasks were performed by the subjects.…”
Section: Analysis and Training Of Sport Skills In Vementioning
confidence: 98%
“…Typical examples exist in rugby Brault et al 2010;Miles et al 2013], handball [Vignais et al 2009;Vignais et al 2010], baseball [Fink et al 2009] or tennis [Xu et al 2009]. Most of these studies aimed at analysing the perception-action coupling without considering the accuracy with which the tasks were performed by the subjects.…”
Section: Analysis and Training Of Sport Skills In Vementioning
confidence: 98%
“…While there are only four articles included in this review, there is an abundance of research assessing sports training in a VE (Bideau et al, 2003; Croft et al, 2011; Zaal and Bootsma, 2011; Marchal-Crespo et al, 2013; Miles et al, 2013), although these studies demonstrate an improvement in the VE-based sport task, the researchers do not assess the impact that the training had on real-world performance. A measure of real-world performance is essential in determining the benefit and value of the training.…”
Section: Resultsmentioning
confidence: 99%
“…Tsai et al also developed a VR system that can simulate basketball tactics from a first-person perspective and showed that this system has advantages in learning complex tactics over the strategy boards used in traditional tactical instruction 9 . Miles et al investigated improving rugby passing skills by projecting stereoscopic images onto a physical screen 10 . One challenge faced by these studies is the limitation on the athlete's physical sensation related to interaction with objects, such as the lack of tactile feedback to the athlete and the learning environment being significantly smaller than the actual court.…”
Section: Introductionmentioning
confidence: 99%